Evaluation of Analgesic, Antipyretic and Anti-Inflammatory Effects of Ethanol Extract from a Fern Species Macrothelypteris Torresiana (Gaudich) Aerial Parts - Mondal, Sumanta; Ghosh, Debjit; Ganapaty, Seru; Manna, Onkar; Reddy, Mora Venkata; Revanth, Vankayalapati (Pharmacognosy Communications)
Introduction: Macrothelypteris torresiana is a species of fern native to tropical and subtropical region and belonging to family Thelypteridaceae. The present study was conducted to evaluate antipyretic, analgesic and anti-inflammatory activities of ethanol extract from Macrothelypteris torresiana aerial parts (EEMTAP) at doses of 200 and 400 mg/kg body weight, per os. Methods: Analgesic activity was evaluated against both thermal and chemical induced stimuli, which were evidenced from tail immersion, formalin induced paw licking and acetic acid induced writhing test. Antipyretic activity was performed by using the yeast induced hyper- pyrexia method. Carrageenan induced rat paw edema and the cotton pellet granuloma model were selected for evaluating anti-inflammatory activities. Results: The formalin study showed that both the aphasic and tonic pain was blocked by the extract. Similarly EEMTAP significantly increased the latency period in the tail immersion test and the assessment of peripheral analgesic effect of the test drug exhibited a significant percentage inhibi- tion in the writhings which were induced by acetic acid in mice. EEMTAP also significantly decreased the rectal temperature of the rats. Carrageenan induced rat paw edema showed that the role of EEMTAP was significant in this acute inflammation model at the tested dose level. In the sub-chronic cotton pellet granuloma model, the tested extract also significantly inhib- ited granuloma formation and the biochemical parameters alanine trans- aminase, aspartate transaminase and alkaline phosphatase in serum. Conclusion: An ethanolic extract of Macrothelypteris torresiana possesses analgesic, anti-inflammatory and antipyretic activity which may be medi- ated by the central and peripheral mechanisms.
Keywords: Aspirin; Ibuprofen; Indomethacin; Macrothelypteris torresiana; Morphine sulphate; Paracetamol